Productive performance of cowpea lines and cultivars cultivated in the second harvest period in Fernandópolis – SP - Garcia, Gustavo Carvalho; Romeiro, Emerson Renato; Matoso, Aline de Oliveira; de Oliveira, Guilherme Montalvão (Seven Editora, 2024)
The correct choice of strains for a given environment and production system is decisive for obtaining high yields. It is important to carry out regional studies, aiming to select superior lines, both for cultivation and for use in genetic improvement programs. The objective of this study was to evaluate the productive performance and morphological characteristics of fifteen lines and five cowpea cultivars of erect and semi-erect size, identifying the most productive cultivars/lines well adapted to the region of Fernandópolis-SP. The work was conducted at the Teaching and Research Farm of the Universidade Brasil, Fernandópolis Campus/SP. The experiment consisted of 20 treatments, 15 lines and 5 upright and semi-erect cowpea cultivars from the Embrapa Mid-North Breeding Program. The experimental design was in randomized blocks with 20 treatments and four replications. The experimental unit consisted of 4 lines with 5 meters in length each with a spacing of 0.50m between rows, and the two central lines were considered as useful area. The following evaluations were carried out during crop development: flowering, average pod length, pod weight, grain weight, number of grains per pod, grain index and grain yield. The data were submitted to analysis of variance using the SISVAR statistical program and the means were compared by the Scott-Knott test at 5% probability. The lines and cultivars showed high precocity in the study region, which is one of the main characteristics needed for cultivation in the second harvest period. Among the genotypes evaluated, MNC04-792F-146, MNC04-795F-153, MNC04-782F-104, MNC04-769F-48, MNC04-769F-62, MNC04-795F-159, MNC04-762F-9 and MNC04-795F-168 stood out, and the cultivars BRS GUARIBA and BRS CAUAMÉ with the highest values for grain yield. The results obtained suggest that it is possible to select productive lines and cultivars for cultivation in the second harvest period in Fernandópolis – SP. DOI:https://doi.org/10.56238/sevened2024.023-025